Teaching Module: Climate Consequences - Sheikh Haniff, Siti Syafinaz Al Khabli; Voon, Qurratul Aini Sherry; Mohammad Namawi, Norazah (Multidisciplinary Applied Research and Innovation, 2021)
My main focus of the study was on the development of the module. In this paper , I focus on showing the consequences on the climate. Global climate change is a phenomenon of gas trapping known as greenhouse gases involving groups of gases (carbon dioxide (CO2), carbon monoxide (CO), chlorofluorocarbons (CFCs), methane, (nitrogen oxides) that prevent and trap the earth’s heat from being released into the space[1]. The earth’s temperature is rising at different rates according to specific continents and regions and the warming of the climate system is no small matter to be ignored [2] Hence, We aim to raise the affect that it haves on our climate. By demonstrating this with the two activities that we created in this teaching module. This module is quite vital because world temperature change is due to continuous global warming. Humans are the cause of climate system disruption and most notably, since the mid-20th century. Hence, alternative methods need to be developed to help the community understand this problem.